(untitled) (Research, Society and Development, 2021)
The adolescence, stage of life represented by moments of discovery, presents itself as emblematic in the social context of drug use, which represents more and more growing each day. Objective: This is a descriptive qualitative study, which aimed to analyze the impact of using psychoactive drugs during adolescence it was executed in the period of March 2021, through an integrative review of the scientific literature. Methodology: The search was carried out on national and international basis, including the Literatura Latino-Americana e do Caribe em Ciências da Saúde (LILACS), SciELO Brasil and PubMED, the search strategy was to use Boolean operators the following Health Sciences Descriptors (DeCS) in Portuguese: Drugs-Adolescents; Psychoactive Substances-Adolescents; Substance Abuse-Adolescents; Drug use-Adolescents. Results: A return of 2122 articles was obtained in the LILACS database, 425 in SciELO Brazil and 96 in PubMED, totaling 2643 articles, and in the delimitation of the inclusion criterion, 35 remained, and only 19 articles were selected to compose the research corpus. It was noticed that the earlier starts the use of psychoactive substances, the more visible are the effects of drugs on long-term behavior. Furthermore, this consumption also includes consequences on the cognitive development of the pubescent, such as a deficit in the learning process. Conclusions: A diversity of factors related to drug use in adolescence were evidenced, among which, the dynamics of family functioning, the cultural context, specific conflicts of this stage of life and socioeconomic condition stood out as the most present trigger pathways for the insertion of adolescents in the world of drugs.